2020
DOI: 10.3390/ijerph18010165
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences on Reproductive Plans and Adolescent Pregnancy in the Gulf Resilience on Women’s Health Cohort

Abstract: We investigated if adverse childhood experiences (ACEs) and ACE sub-types were associated with increased odds of planning to have children and adolescent pregnancy. The Gulf Resilience on Women’s Health (GROWH) is a diverse cohort of reproductive-age women living in southeastern Louisiana during the 2010 Deepwater Horizon oil spill. In our sample of 1482 women, we used multinomial logistic regression to model odds ratios of wanting future children and assessed effect measure modification by educational attainm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
0
3
0
5
Order By: Relevance
“…Çocuklukta önemli bir stres etkeni olan ÇÇOY, erken puberte (Zhang vd., 2019), premenstruel sendrom (Özşahin, Ünver ve Güven Santur, 2022), adölesan gebelik (Flaviano ve Harville, 2021), erken menapoz, preterm ve ölü doğum (Demakakos vd., 2020), gebelikte stres (Özşahin, 2020;Wajid, 2020), postpartum depresyon (Özşahin ve Güven Santur, 2021) gibi birçok soruna yol açtığı belirtilmektedir. Bu nedenle bu çalışmanın amacı ÇÇOY'nin gebelikteki yakınmalar ve yaşam kalitesine etkisini belirlemek ve sağlık profesyonellerinin bu travmaların etkisine dikkat çekmektir.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Çocuklukta önemli bir stres etkeni olan ÇÇOY, erken puberte (Zhang vd., 2019), premenstruel sendrom (Özşahin, Ünver ve Güven Santur, 2022), adölesan gebelik (Flaviano ve Harville, 2021), erken menapoz, preterm ve ölü doğum (Demakakos vd., 2020), gebelikte stres (Özşahin, 2020;Wajid, 2020), postpartum depresyon (Özşahin ve Güven Santur, 2021) gibi birçok soruna yol açtığı belirtilmektedir. Bu nedenle bu çalışmanın amacı ÇÇOY'nin gebelikteki yakınmalar ve yaşam kalitesine etkisini belirlemek ve sağlık profesyonellerinin bu travmaların etkisine dikkat çekmektir.…”
Section: Discussionunclassified
“…Araştırmaya katılan gebelerin yaş ortalamasının 28.74±5.10 olduğu ve %18.2'sinin 1. maddeye, %10.4'ünün 2. maddeye, %3.3'ünün 3. maddeye, %12.2'sinin 4. maddeye evet dediği ve %5.9'unun 7. maddeye evet dediği belirlenmiştir. Yapılan bir çalışmada en fazla yaşanan şiddet türünün parçalanmış aile ve sözel şiddete maruziyetin olduğu (Jelley vd., 2020), başka bir çalışmada duygusal ve fiziksel ihmalin daha fazla olduğu (Cohrdes ve Mauz, 2020), farklı bir çalışmada ihmal ve duygusal şiddetin daha fazla yaşandığı belirtilmektedir (Flaviano ve Harville, 2021). Bulgumuz literatürle benzerlik göstermektedir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Weakening the immune system upon pregnancy makes pregnant women more sensitive to the effect of different potentially toxic materials, including conventional polymers [3]. Many conventional synthetic or petroleum-based polymer-based materials are widely used in pregnant women's daily lives, confirmed by many epidemiological and human monitoring studies their ability to cause serious health issues, including cancers [4][5][6]. The toxic effect of these materials is restricted to pregnant women, but it has been confirmed that such materials can induce genetic alterations, which may lead to a significant genetic deformity in future generations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They are usually in place well before pregnancy, so that pregnancy begins under less optimal conditions and potentially leads to chronic diseases for both mother and child [ 7 ]. In addition, social class, stress, and trauma, whenever experienced, affect both biology and behavior, with consequences for pregnancy health, fecundability, and fertility decisions [ 8 ]. Developmental Origins of Health and Disease theory and research, while primarily focused on cardiometabolic health, also have been applied to reproductive outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%